SPIRITUALITAS KRISTEN DALAM BAYANG-BAYANG VIRTUALITAS: MENAFSIR KEHADIRAN ILAHI DAN TANGGUNG JAWAB ETIS GEREJA DI ERA DIGITAL GLOBAL - Altin Sihombing (Manna Rafflesia, 2025)
Digital transformation has presented new challenges for the church in maintaining Christian spirituality in line with biblical values in the midst of an instant and fragmented virtual space. In the era of digital globalisation, the divine presence in worship practices and online communities is no longer physical but mediated by technology, which has the potential to obscure the meaning of incarnational spirituality. This study aims to re-narrate the presence of God and formulate the ethical responsibility of the church in building contextual digital spirituality. The study employs a qualitative method based on literature review, leading to the conclusion that Christian spirituality and divine presence must be re-narrativised as an expression of incarnational theology in the virtual realm, enabling the church to present divine reality in a transformative manner within the digital world. In this context, Christian ethics serve as the primary foundation for the church's responsibility in building a healthy, integrity-driven, and spiritually unmanipulated digital ecology. The virtual disruption that has occurred not only changes the form of ministry but also gives rise to a spiritual crisis that directly impacts the process of faith formation among the faithful in the digital age. Therefore, a contextual church strategy is needed to formulate a digital spirituality that remains incarnational, relevant, and capable of guiding the faithful toward a genuine encounter with God in their daily lives that have been digitised. The church must also be an ethical agent in the digital space, rejecting the manipulation and commercialisation of faith. In this way, digital spirituality can become a vessel for authentic and prophetic growth in faith.